PENGEMBANGAN PERIKANAN - Meyzi Heriyanto, Wira Sastra, Sujianto, (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Fisheries Development. The research objective is to determine the implementation of development in Kampar District. The research informants were the Head, Secretary and Head of Section, Head of Section and Head of Subdivision of the Head of Regional Office, Members of DPRD, UPT Train and Fish Culture Development Farmer Group. Data collection techniques are interviews and observation. Data analysis through data collection, data reduction and conclusion drawing. Factors that influence Fisheries Development in Kampar Regency consist of Conflicting Goals, Communication factors, Conflicting factors which are suppressed Cooperation Factors, Competition Factors, Decision Making factors, Response factors to Changes As well as in efforts to increase motivation can be done is to optimize staff performance .